2008
DOI: 10.1111/j.1558-5646.2008.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Postcopulatory Sexual Selection Reduces the Intramale Variation in Sperm Design

Abstract: Sperm competition is an important force driving the evolution of sperm design and function. Inter-and intraspecific variation in sperm design are strongly influenced by the risk of sperm competition in many taxa. In contrast, the variation among sperm of one male (intramale variation) is less well understood. We investigated intramale variation in sperm design in passerine birds and found that risk of sperm competition is negatively associated with intramale variation. This result is the first clear evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(140 citation statements)
references
References 52 publications
14
126
0
Order By: Relevance
“…Theoretical models also predict lower variation in sperm dimensions within males under strong sperm competition levels [29,30]. In line with these predictions, comparative studies have shown a strong inverse relationship between sperm competition indices and coefficients of both between-male (CV bm ) and within-male (CV wm ) variation in sperm length in insects [31] and birds [32,33]. In contrast to sperm CV wm , the relationship between sperm CV bm and sperm competition risk does not show any phylogenetic bias (cf.…”
Section: Introductionmentioning
confidence: 61%
“…Theoretical models also predict lower variation in sperm dimensions within males under strong sperm competition levels [29,30]. In line with these predictions, comparative studies have shown a strong inverse relationship between sperm competition indices and coefficients of both between-male (CV bm ) and within-male (CV wm ) variation in sperm length in insects [31] and birds [32,33]. In contrast to sperm CV wm , the relationship between sperm CV bm and sperm competition risk does not show any phylogenetic bias (cf.…”
Section: Introductionmentioning
confidence: 61%
“…To elucidate the origin of these patterns comparative analyses in different bird groups have suggested that betweenindividual variation in sperm size is most pronounced in species subject to low levels of sperm competition, probably due to relaxed selection on an optimal sperm morphometry and so too presumably on other aspects of spermatogenesis (Birkhead et al, 2005;Calhim, Immler & Birkhead, 2007;Kleven et al, 2008;Lüpold, Linz & Birkhead, 2009a). Moreover, there may also be a role for post-mating sexual selection in explaining patterns of within-individual variation in sperm morphometry, since bird species subject to high levels of sperm competition are also those that show the lowest levels of standardised within-individual variation in sperm size (Immler, Calhim & Birkhead, 2008), which has led to the suggestion that sperm competition may select for enhanced quality control during spermatogenesis (see also Lüpold et al, 2011).…”
Section: (2) Variation and Plasticity In Sperm Morphology Within Speciesmentioning
confidence: 99%
“…Marked phenotypic variation across sperm cells within a single ejaculate is ubiquitous, both in terms of sperm morphology [6][7][8] and performance [9]. However, sperm are generally considered products of the diploid paternal genome with no endogenous haploid gene expression, and sperm phenotype is thus thought not to reflect the haploid genome they carry [10].…”
Section: Introductionmentioning
confidence: 99%